Detecting structural connectivity of the brain using DTI images - Lim, Gisela Xin Er (2017)
Alzheimer’s disease is a progressive brain disease and the sixth-leading cause of death in the United States, according to the Centers for Disease Control and Prevention . This poses a major problem as there is no cure for the illness. To know the differences between healthy brains and brains with Alzheimer disease in terms of their white matter connectivity and white matter tracts can provide breakthrough in the field of neurology and bioinformatics. Determining white matter impairments in Alzheimer’s disease brains can help shed some light to the reason behind this disease and solutions that can solve it. Structural connectivity of brains is crucial to understand how the brain functions. The structural connections of the brain can be measured using Diffusion Tensor Imaging (DTI).